2021
DOI: 10.1111/jnc.15488
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of olfactory sensory neurons to food cues is tuned to nutritional states by Neuropeptide Y signaling

Abstract: Modulation of sensory perception by homeostatic feedback is critical for survival. Gating of sensory inputs by internal states, such as energy availability, enables the animal to issue measured responses, like food-seeking and consumptive behaviors. Olfaction is an important sensory modality in food-seeking behavior providing predictive information on the availability, quality, and associated reward

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…This expression is consistent with other studies in teleosts for npy (Cerdá-Reverter et al, 2000;Gaikwad et al, 2004;Kaniganti et al, 2021;Pirone et al, 2008;Porter et al, 2017) and cart or cart2b (Akash et al, 2014;Bonacic et al, 2015;Kalananthan et al, 2021;Le et al, 2016). Interestingly, fasted zebrafish express higher levels of npy in the olfactory bulb compared to those fed (Kaniganti et al, 2021), while in Atlantic salmon fasting decreased npya1 and increased cart2b mRNA levels in the olfactory bulb (Kalananthan et al, 2021;Tolås et al, 2021). In fact, npy has been suggested to serve as a neurotransmitter, while cart is involved in modulating the activity that (Akash et al, 2014;Gaikwad et al, 2004;Kalananthan et al, 2021;Kaniganti et al, 2021;Singru et al, 2008;Tolås et al, 2021).…”
Section: Expression Of Melanocortin System Neuropeptides In Other Bra...supporting
confidence: 91%
See 1 more Smart Citation
“…This expression is consistent with other studies in teleosts for npy (Cerdá-Reverter et al, 2000;Gaikwad et al, 2004;Kaniganti et al, 2021;Pirone et al, 2008;Porter et al, 2017) and cart or cart2b (Akash et al, 2014;Bonacic et al, 2015;Kalananthan et al, 2021;Le et al, 2016). Interestingly, fasted zebrafish express higher levels of npy in the olfactory bulb compared to those fed (Kaniganti et al, 2021), while in Atlantic salmon fasting decreased npya1 and increased cart2b mRNA levels in the olfactory bulb (Kalananthan et al, 2021;Tolås et al, 2021). In fact, npy has been suggested to serve as a neurotransmitter, while cart is involved in modulating the activity that (Akash et al, 2014;Gaikwad et al, 2004;Kalananthan et al, 2021;Kaniganti et al, 2021;Singru et al, 2008;Tolås et al, 2021).…”
Section: Expression Of Melanocortin System Neuropeptides In Other Bra...supporting
confidence: 91%
“…The topology of central neuropeptides of the melanocortin system has been mapped in the whole brain or in specific brain regions in several teleost species, including catfish Clarias batrachus (Gaikwad et al., 2004 ; Singru et al., 2008 ; Subhedar et al., 2011 ), Indian major carp Cirrhinus cirrhosus (Saha et al., 2015 ), goldfish Carassius auratus (Cerdá‐Reverter & Peter, 2003 ; Cerdá‐Reverter, Schiöth, et al., 2003 ; Kojima et al., 2010 ; Matsuda et al., 2009 ), zebrafish (Akash et al., 2014 ; Forlano & Cone, 2007 ; Jeong et al., 2018 ; Kaniganti et al., 2021 ; Koch et al., 2019 ; Mukherjee et al., 2012 ; Shainer et al., 2017 , 2019 ), sea bass Dicentrarchus labrax (Agulleiro et al., 2014 ; Cerdá‐Reverter et al., 2000 ), Atlantic cod Gadus morhua (Le et al., 2016 ), and the African cichlid fish Astatotilapia burtoni (Porter et al., 2017 ). However, to our knowledge, coexpression of npy/agrp and cart/pomc in the hypothalamus has never been observed in a teleost species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although details of the sophisticated olfactory signal processing remain largely unknown, it has been suggested that NPY, which is extensively expressed in the fish OB, plays an important regulatory role in this process. , According to the data obtained, 28 day exposure of goldfish to 30 ng L –1 FLX resulted in a significant decline in NPY (indicated by NPY-specific immunofluorescent staining), which could also interfere with olfactory signal processing by disrupting NPY regulation.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Subsequently, the olfactory signal will be processed by the olfactory bulb (OB) of the fish brain under the regulation of multiple neuromodulators, such as neuropeptide Y (NPY). 21 To efficiently capture environmental chemosensory information, the OE of fish is fully exposed to the surrounding water and thus susceptible to waterborne contaminants (i.e., pollutants may hamper the normal function of OE such as the initiation of olfactory signals by inducing oxidative damage). 22 In addition, due to the high affinity of 5-HT transporters of fish species for FLX, 23 the olfactory signal transmission of fish, which is mediated by neurotransmitters including 5-HT, might be a potential target of FLX as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation